33. CURRENT STATUS OF NUTRITIONAL ACTIVITIES IMPLEMENTATION AT DISTRICT GENERAL HOSPITALS IN THANH HOA PROVINCE IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current status of nutrition activities for patients at district general hospitals, Thanh Hoa province in 2024.Method: A cross-sectional descriptive study was conducted at 27 district general hospitals in Thanh Hoa province from June to December 2024. Data was collected using structured questionnaires through direct interviews with hospital nutrition departments.Results: Among 27 district general hospitals in Thanh Hoa province, 12 hospital (44.4%) had established nutrition departments. Each department had an average of 3.07 ± 1.89 staff members, with 70.1% led by nurses, of whom 63% worked part-time. Most hospitals lacked adequate equipment for nutritional assessment and services. Only 11.1% of patients received disease-appropriate meals, and 29.6% received nutritional counseling or supervision.Conclusion: Hospitals lack qualified staff, especially doctors and nutritionists, as well as necessary facilities and equipment for nutrition services. Nutritional practices remain below the Ministry of Health standards.
Keywords: Nutrition and dietetic nutrition; hospital